"Narratives of our past:" Taking a journey through history for collective well‐being. Issue 4 (15th July 2018) - Ho, Elaine Qiao‐Ying; Leong, Chan‐Hoong; Lim, Varian
Abstract : Past research on life satisfaction is examined mostly at the individual level and with attention to the influence of demographics, personality, and intergroup factors. There has been little, if any, research on how historical narratives affect subjective satisfaction. The current study interviewed a national sample of 1, 516 Singapore citizens on how they perceive the history of Singapore. The results identified three distinct narratives that can be broadly themed as Nation‐Building, Conflicts and Contestations, and National Resilience events. Further analyses using hierarchical linear regression models showed that these events vary in their relationships to present and future life satisfaction, after controlling for past/current satisfaction and demographics. Interestingly, the Nation‐Building narrative positively predicted present life satisfaction and negatively predicted future satisfaction. The narrative measuring National Resilience was positively linked to perceived current and future life satisfaction. The Conflicts and Contestations narrative, however, inversely predicted current life satisfaction only. The findings suggest that social constructions of history and shared memories provide a roadmap to understanding psychological well‐being, sense of nationhood, and social resilience at the national level.